Long Night's Journey Into Day - Reid, Francis; Hoffman, Deborah (United States, 2000)
Soros Documentary Fund The film presents South Africa's quest for restorative justice after Apartheid as it follows four dramatically different cases at the Truth and Reconciliation Commission over the course of two-and-a-half years. White soldiers who have killed ANC activists, black activists who have killed whites in political attacks: can there be forgiveness when the full truth comes out?